Comparison of Household Transmission of Influenza Virus From Index Patients Treated With Baloxavir Marboxil or Neuraminidase Inhibitors: A Health Insurance Claims Database Study. (26th October 2020) - Komeda, Takuji; Takazono, Takahiro; Hosogaya, Naoki; Ogura, Eriko; Fujiwara, Masakazu; Miyauchi, Hideyuki; Ajisawa, Yoshikazu; Iwata, Shinpei; Watanabe, Hideaki; Honda, Keiichi; Kitanishi, Yoshitake; Hara, Kanae; et al.
Abstract: Background: Baloxavir marboxil (baloxavir) is expected to reduce influenza transmission by rapid reduction of viral load. The incidence of household transmission was compared between index patients (IPs) treated with baloxavir and those treated with neuraminidase inhibitors. Methods: Using a Japanese claims database, the first family members with influenza diagnosis during the 2018–2019 influenza season were identified as IPs, and the diagnosis date was designated day 1. According to the anti-influenza drug dispensed to the IP, their families were classified into the oral baloxavir group and 3 controls: oral oseltamivir group (a primary control), inhaled zanamivir group, and inhaled laninamivir group. A household transmission was defined as influenza diagnosed for any non-IP family members during days 3−8. The incidence of household transmission was compared between groups using a logistic regression model adjusting backgrounds of IPs. Results: The proportion of families with household transmission was 17.98% (15 226 of 84 672) in the baloxavir group and 24.16% (14 983 of 62 004) in the oseltamivir group. The covariate-adjusted odds ratio (oseltamivir/baloxavir) was 1.09 (95% confidence interval [95% CI], 1.05–1.12), which indicated significantly lower incidence in the baloxavir group. The adjusted odds ratios (controls/baloxavir) against zanamivir and laninamivir were 0.93 (95% CI, .89–.97) and 0.99 (95% CI, .96–1.02), respectively. Conclusions: Baloxavir may contribute to reduction in household transmission compared with oseltamivir. In comparison between baloxavir and inhalants, a similar reduction was not shown and it might be due to unmeasured confounding by administration route differences. Abstract : Treatment of index patients with baloxavir marboxil results in a significantly lower incidence of household transmission compared with treatment with oseltamivir. Baloxavir marboxil reduces viral shedding and may help to reduce the risk of infection spread.